2009
DOI: 10.1215/15228517-2009-001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of regions correlating MGMT promoter methylation and gene expression in glioblastomas

Abstract: The O(6)-methylguanine-DNA methyltransferase gene (MGMT) is methylated in several cancers, including gliomas. However, the functional role of cysteine-phosphate-guanine (CpG) island (CGI) methylation in MGMT silencing is still controversial. The aim of this study was to investigate whether MGMT CGI methylation correlates inversely with RNA expression of MGMT in glioblastomas and to determine the CpG region whose methylation best reflects the level of expression. The methylation level of CpG sites that are pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
156
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(170 citation statements)
references
References 32 publications
(58 reference statements)
12
156
0
1
Order By: Relevance
“…Everhard et al reported CpG sites at +95, +113, +135 and +137 bp from the transcriptional start site (TSS) (CpG 1, 3, 7 and 8 in our study, respectively) and high concordance between methylation and expression of MGMT in their analysis of 53 CpG sites in 54 glioblastoma samples (15). Malley et al reported that individual or multiple consecutive methylation of CpG sites at +153, +185, +195 and +213 bp from the TSS (CpG 11, 14, 15 and 17 in our study, respectively) attenuated the activity of the MGMT promoter in their study of 98 CpG sites in xenografted glioblastoma samples and cell lines (6).…”
Section: Cpg Site ---------------------------------------------------supporting
confidence: 59%
See 1 more Smart Citation
“…Everhard et al reported CpG sites at +95, +113, +135 and +137 bp from the transcriptional start site (TSS) (CpG 1, 3, 7 and 8 in our study, respectively) and high concordance between methylation and expression of MGMT in their analysis of 53 CpG sites in 54 glioblastoma samples (15). Malley et al reported that individual or multiple consecutive methylation of CpG sites at +153, +185, +195 and +213 bp from the TSS (CpG 11, 14, 15 and 17 in our study, respectively) attenuated the activity of the MGMT promoter in their study of 98 CpG sites in xenografted glioblastoma samples and cell lines (6).…”
Section: Cpg Site ---------------------------------------------------supporting
confidence: 59%
“…Furthermore, as MGMT promoter methylation is inversely correlated with MGMT expression (5,6), methylation-specific PCR (MSP) with bisulfate-treated DNA has been widely used to analyze MGMT promoter methylation status (7)(8)(9). However, MSP is only able to detect a limited number of methylated CpG sites in the primer region, and recent studies report that the region commonly investigated by MSP does not cover CpG sites that are most highly associated with expression of MGMT, and that MSP may not be well-suited for predicting the prognosis of patients with glioblastoma (15,16). Direct sequencing and pyrosequencing are alternative methods for quantitatively analyzing the methylation status of MGMT.…”
Section: Cpg Site ---------------------------------------------------mentioning
confidence: 99%
“…16 Some studies have provided insight into the relationship between gene expression and the patterns and localization of dense CpG methylation in the MGMT promoter. 16,17 Two regions that are prone to high levels of methylation have been identified, of which the region comprising the enhancer element seems to be more critical for the loss of MGMT gene expression upon methylation, on the basis of luciferase reporter assays interrogating different regions of the methylated promoter. 16,17 Hence, most methylation-specific tests are designed to interrogate this region ( Figure 2b).…”
Section: The Mgmt Gene and Its Promotermentioning
confidence: 99%
“…3 MGMT expression is mainly regulated at the epigenetic level through CpG island promoter methylation. 4,5 Promoter methylation tests are thus used for MGMT assessment at the DNA level. Most studies reporting a link between MGMT promoter methylation and survival in GBM patients have used methylation-specific polymerase chain reaction (MS-PCR).…”
Section: Introductionmentioning
confidence: 99%